Penetapan Kadar Inulin dalam Ekstrak Air Umbi Bengkuang (Pachyrhizus erosus L.) dari Gresik Jawa Timur dengan Metode KLT Densitometri (Inulin Determination of Yam Bean Tuber (Pachyrhizus erosus L.) from Gresik East Java using TLC Densitometry) - Marizka Wimala; Yuni Retnaningtyas; Lestyo Wulandari (Pustaka Kesehatan, 2015)
Yam bean is one of tubers group that has many benefits because of its chemical constituents named inulin. Yam bean are produced in several regions in Indonesia such as Tegal, Bogor, Prembun, and Madura. In this research, inulin determination in yam bean tuber from Gresik East Java as one of yam bean production center, performed to obtain the plant source in Indonesia which is potential to produce inulin. Inulin determination was conducted using TLC Densitometry method that has been validated. Based on a standard curve that meets the requirements of linearity (r=0,997; Vxo=3,847%; Xp=355,407ng), the results showed that levels of inulin in yam bean tuber derived from Gresik was 12,322%±1,733% and mean recovery was 100,08% ± 1,142%. This result meet the requirements for the actual analyte concentration ≥10%: coefficient of variation is